Implementation of Amino Acid as a Natural Feedstock in Production of N-Acylamides as a Biocompatible Surfactants: A Review on Synthesis, Behavioral, Application and Scale-up Process - Widharta Surya Alam; Sabila Gitamara; Riki Wartakusumah; Muhammad Irfan Nurdin; Zuhrina Masyithah (Chemistry Department, The University of Brawijaya, 2022)
The use of surfactants is extremely widespread for human life. The development of the use of surfactants has not reached detergents anymore, but for drug delivery, biolubricant, emulsifier, cosmetics, enhanced oil recovery (EOR), dispersants and even virus vectors. Unfortunately, the past history of surfactants had given a bad impression since many surfactants are difficult to decompose in nature, are toxic and are not suitable as biological materials. This article will examine the research development and production, syntesis pathway, classification, behaviour and application of N-Acyl amino acid (NAAAc) surfactants. Amino acid based N-Acylamides (AAc) or NAAAc surfactants are next-generation biological surfactants. NAAAc can be synthesized by chemical and enzymatic pathway. NAAAc can also be combined with ionic liquids (ILs) to become green surfactants NAAAc ILs which is low in toxicity unlike conventional ILs. The conclusion of this article studied was NAAc production process that had the highest efficiency so far was the production through a catalytic chemical reaction, namely the fatty acid amidation or amino acid acylation process. The application of AAc-based N-Acylamides is so promising that it can be considered for scale-up processes in the future.